An esterase-activatable curcumin prodrug for tumor-targeting therapy. Issue 96 (14th November 2022) - Liu, Li; Zhang, Lele; Tao, Menglin; Wang, Minghui; Dong, Ling; Hai, Zijuan
Abstract : Armed with a tumor-targeting RGD peptide and an in situ esterase-triggered drugrelease, prodrug Cur-RGD can efficiently improve the therapeutic effect ofcurcumin in tumors. Abstract : A tumor-targeting therapy strategy is urgently needed to increase the accumulation of drugs in tumors and reduce the side effects in normal tissues. Herein, we developed an esterase-activatable curcumin prodrug Cur-RGD for tumor-targeting therapy. Armed with the tumor-targeting RGD peptide and in situ esterase-triggered drug release, this prodrug Cur-RGD can efficiently improve the therapeutic effect of curcumin in tumors.